2020
DOI: 10.1186/s13071-020-04263-3
|View full text |Cite
|
Sign up to set email alerts
|

Semi-field evaluation of freestanding transfluthrin passive emanators and the BG sentinel trap as a “push-pull control strategy” against Aedes aegypti mosquitoes

Abstract: Background: Spatial repellents that drive mosquitoes away from treated areas, and odour-baited traps, that attract and kill mosquitoes, can be combined and work synergistically in a push-pull system. Push-pull systems have been shown to reduce house entry and outdoor biting rates of malaria vectors and so have the potential to control other outdoor biting mosquitoes such as Aedes aegypti that transmit arboviral diseases. In this study, semi-field experiments were conducted to evaluate whether a push-pull syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
7
15
0
Order By: Relevance
“…Eave-positioned targeted insecticide (EPTI) emanators comprising 4 m × 0.1 m strips of hessian treated with 5 g, 10 g, 15 g, or 20 g of transfluthrin [27] were used for the experiments with Anopheles. For Aedes mosquitoes, freestanding transfluthrin passive emanators (FTPEs) [28] comprising 5 m × 0.1 m hessian strips treated with the same four doses of transfluthrin were used. Negative controls were prepared in the same way with water.…”
Section: Preparation Of the Transfluthrin Passive Emanatormentioning
confidence: 99%
See 1 more Smart Citation
“…Eave-positioned targeted insecticide (EPTI) emanators comprising 4 m × 0.1 m strips of hessian treated with 5 g, 10 g, 15 g, or 20 g of transfluthrin [27] were used for the experiments with Anopheles. For Aedes mosquitoes, freestanding transfluthrin passive emanators (FTPEs) [28] comprising 5 m × 0.1 m hessian strips treated with the same four doses of transfluthrin were used. Negative controls were prepared in the same way with water.…”
Section: Preparation Of the Transfluthrin Passive Emanatormentioning
confidence: 99%
“…Of these outcomes, only repellence can be appropriately evaluated by HLC, as only mosquitoes that land are taken into consideration in the analysis. Other outcomes such as mortality or knock-down may not be fully assessed by HLC [28,45], as mosquitoes will spend more time in contact with the treated device while blood-feeding, which may increase mortality. Conversely, blood-fed mosquitoes show enhanced survival when exposed to pyrethroids [52].…”
Section: Use Of the I-lact Bioassay For The Measurement Of Additional...mentioning
confidence: 99%
“…This risk could theoretically be reduced if SR use is combined with push-pull strategies, notably those in which SRs (push) are paired with traps containing CO 2 or other attractants (pull) [ 59 ]. However, several studies have found that such combined approaches do not work better than the use of repellents alone [ 60 , 61 , 62 ], so further community-level research is merited.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread reports of insecticide resistance indicate threats to public health anti-vector programmes (1,2). In response, at least in part, alternative insecticide-based tools for public health have been further explored, with increasing interest in pyrethroid-based ambient insecticides such as spatial repellents (3)(4)(5). Herein, ambient insecticides refer to aerosolized and volatile insecticides (spatial repellents) deployed by candles, mats, emanators, sprays and coils.…”
Section: Introductionmentioning
confidence: 99%